2006
DOI: 10.1002/aic.11029
|View full text |Cite
|
Sign up to set email alerts
|

Liquid‐liquid two‐phase flow patterns in a rectangular microchannel

Abstract: in Wiley InterScience (www.interscience.wiley.com).In this work, the flow of immiscible fluids in a PMMA microchannel 300 mm wide and 600 mm deep was investigated experimentally. Dyed de-ionized water and kerosene were selected as the test fluids. Flow patterns were observed by using a CCD camera and were identified by examining the video images. Flow patterns obtained at the T-junction and in the microchannel are presented. Superficial velocities varied between 9.26 Â 10 À4 ; 1.85 m/s for water and 9.26 Â 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
234
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 295 publications
(249 citation statements)
references
References 32 publications
13
234
1
1
Order By: Relevance
“…These results were validated with the experimental results of Tice et al 22 Yong et al 25 numerically studied the immiscible kerosene-water two-phase flows in a T-junction microchannel using a Lattice Boltzmann (LB) method. This result quantitatively and qualitatively verified the experimental results of Zhao et al [14][15][16] and justified the effectiveness of the numerical method. Further, the effect of interfacial tension and contact angle on the flow patterns and droplet shapes were investigated, and highlighted the numerical results based on the improved two-phase LB model.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…These results were validated with the experimental results of Tice et al 22 Yong et al 25 numerically studied the immiscible kerosene-water two-phase flows in a T-junction microchannel using a Lattice Boltzmann (LB) method. This result quantitatively and qualitatively verified the experimental results of Zhao et al [14][15][16] and justified the effectiveness of the numerical method. Further, the effect of interfacial tension and contact angle on the flow patterns and droplet shapes were investigated, and highlighted the numerical results based on the improved two-phase LB model.…”
Section: Introductionsupporting
confidence: 80%
“…The flow pattern and droplets formation mechanism of dispersed phase have been experimentally studied by several authors, who have discussed the flow regimes in microchannels viz. mono-dispersed drop flow, slug flow, parallel flow based on the Weber numbers of fluid phases [14][15][16][17] . The free surface simulation has been carried out by Kashid et al 18 to understand the mechanism of slug flow generation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the interfacial tension dominates the inertia forces producing slugs. Zhao et al (2006) showed that if inertia forces dominate (We > 10), the turbulence appears and chaotic or annular flow are observed.…”
Section: Analysis Of the Flow Patterns Based On Capillary And Reynoldmentioning
confidence: 99%
“…The effects of the linear velocity, the channel diameter and the ratio of the volumetric flow rates on the stability of the slug flow regime were represented in a flow pattern map. Zhao et al (2006) investigated the stability of different flow patterns using a T-junction rectangular microreactor made of PMMA with deionised water and kerosene. In the flow pattern map, the phase Weber numbers (Table 1) were used.…”
Section: Introductionmentioning
confidence: 99%
“…For all the experiments reported, the mean Weber numbers are smaller than 1. Therefore, the interfacial tension dominates the inertia forces producing slugs (Zhao et al, 2006). It showed that if inertia forces dominate (We >10), the turbulence appears and annular flows are observed.…”
Section: Discussionmentioning
confidence: 96%